Dynamic Capabilities and Digital Transformation: Toward Strategic Planning in the Digital Age—Evidence from Palestine - Yamin Abu Alrub; Sandra M. Sánchez-Cañizares (Administrative Sciences)
The concept of digital maturity has gained prominence in the context of digital transformation. It refers to an organization’s ability to effectively adapt to changing environments using digital technologies. At the same time, the dynamic capabilities of an organization play a crucial role in maintaining a competitive advantage. These capabilities allow organizations to integrate, build, and reconfigure competencies in response to market dynamics. Despite empirical evidence supporting the impact of dynamic capabilities on competitive advantage, there remains a need to explore the specific mechanisms driving this relationship. Moreover, in traditional industries experiencing digital disruption, understanding digital maturity as an intermediate outcome becomes essential. This study focuses on the Palestinian financial sector and investigates the significance of digital maturity in the context of dynamic capabilities. Primary data were collected through an online questionnaire survey, and a model was estimated through a SEM-PLS methodology. The results highlight a strong relationship between dynamic capability and competitive advantage. Thus, digital maturity plays a crucial role in enhancing strategic planning efficiency through the implementation of dynamic capabilities.